Assessment of DNA barcoding regions for identification of Malaysian banana cultivars - Zulkifli, Abdul Rahman (2013)
To date, there is no exclusive barcode for bananas and plantains being documented, hence, this study was undertaken to find out the most suitable barcodes for banana cultivars identification. The aim of this study was to determine the most appropriate DNA regions to be assigned as the DNA barcoding for banana cultivars identification. In this study, genes from chloroplast genome were chosen as the barcode candidates, namely matK, rpoB, rpoC1, rbcL, trnH-psbA primers and their combinations. In addition, ITS2 gene from nuclear genome was also selected. Six banana cultivars, namely Pisang Jari Buaya, Pisang Raja Udang, Pisang Tanduk, Pisang Rastali, Pisang Nangka and Pisang Nipah were sampled from UPM banana germplasm collection, located in Kompleks Ladang Bersepadu, Taman Pertanian Universiti, Universiti Putra Malaysia. Four criteria have been used to assess the barcoding properties of the chosen barcode regions, i.e. the ability to be screened and amplified from the whole genome, their genetic divergence characteristic, the ability to form monophyletic clade, and the DNA barcoding gap. By using the suggested primer pairs, Polymerase Chain Reaction (PCR) technique was employed to screen and amplify the desired regions. The genetic divergence characteristic, inter and intraspecific genetic distances were assessed from the genetic distance matrices based on Kimura 2 Parameter model using MEGA5 software. The monophyletic clade assessment was done following phylogenetic technique. The phylogenetic trees involved were inferred using Neighbour Joining (NJ), Maximum Parsimony (MP), Maximum Likelihood (ML) and Bayesian Inference (BI) methods. As for the DNA barcoding gap, the data from previous genetic distance matrices were used and the graphs were created using Microsoft Excel 2007 software. The assessment revealed that the used primers generally performed well in PCR amplification with the average PCR efficiency of 89%. However, ITS2 showed that it was the easiest marker to work with. On the other hand, trnH-psbA has the highest interspecific divergence and the lowest intraspecific divergence (0.0261 and 0.000 respectively). For phylogenetic analysis, ITS2 managed to resolve monophyletic clades for all cultivars, which were strongly supported by bootstrap and posterior probability values. Nevertheless, none of the barcode candidates exhibited clear “barcoding gap”. In conclusion, this study revealed that chloroplast genome was not suitable for identification of hybrid plants, such as banana cultivars, because it only can elucidate a single line of genetic inheritance since chloroplast mode of inheritance only either through paternal or maternal line. Nuclear gene, ITS2, was shown to be the best candidate for highly hybrid plants such as banana cultivars. Thus, this study suggested that ITS2 region to be used for DNA barcoding of Malaysian banana cultivars. For future study, the number of cultivars should be increased and Single Nucleotide Polymorphism (SNP) marker can be established based on the barcoding region. By employing High Resolution Melting temperature (HRM) technique, faster, rapid and high throughput identification can be possible.